1988
DOI: 10.1002/iroh.19880730607
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐Sea Polychaetous Annelida from Central America to the Antarctic Peninsula and South Sandwich Islands

Abstract: Based on the 1958 Vema cruise and the 1965 Anton Bruun cruise 11 off the west coast of Central America and sout'h through the islands ezst of the tip of South America, 143 trawl samples were examined for abyssal polychaetous annelida. The cruise tracks designated 7 major areas: Central America (I), Ecuador-Peru (11), Central and Southern Chile (111), Chile and the Magellan Strait (IV), Tierra del Fuego (V), the Island Complex (Falkland, South Georgia and South Sandwich Islands) (VI), the Dribke Strait and Anta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In contrast, Ophelina species are mainly present on deeper bottoms of the continental shelf and slope where they can become one of the most relevant faunal components (Cúrdia et al 2004;Maurer and Williams 2007;Schüller and Ebbe 2007). The knowledge of the actual diversity and ecology in this genus has improved in the last decades Hartmann-Schröder and Parker 1995;Maciolek and Blake 2006;Schüller 2008), mostly due to the study of material collected in several research projects devoted to the knowledge of the deep-sea fauna (e.g.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, Ophelina species are mainly present on deeper bottoms of the continental shelf and slope where they can become one of the most relevant faunal components (Cúrdia et al 2004;Maurer and Williams 2007;Schüller and Ebbe 2007). The knowledge of the actual diversity and ecology in this genus has improved in the last decades Hartmann-Schröder and Parker 1995;Maciolek and Blake 2006;Schüller 2008), mostly due to the study of material collected in several research projects devoted to the knowledge of the deep-sea fauna (e.g.…”
Section: Discussionmentioning
confidence: 91%
“…Mann-Whitney U-test for differences in density, species richness, diversity and evenness values (means ± SD) between the Magellan region (MR) and Weddell Sea ( The actual patterns derived from this study are based on 163 species and 36 families in WS, and 199 species and 37 families in MR. The latter figures represent the highest numbers of species/families reported up to now for the little studied MR. Maurer & Williams (1988) reported 76 polychaete species belonging to 33 families for the Straits of Magellan, while Cañete et al (1999) distinguished 38 species from 24 families in 39 corer samples from the northern border of MR. Bremec et al (2000) found 119 polychaete species from 34 families in the Straits of Magellan and 36 species from 20 families on the eastern Patagonian shelf in their qualitative and quantitative samples.…”
Section: Discussionmentioning
confidence: 99%
“…If Aedicira nr. ramosa sensu Maurer and Williams (1988) is a different species, the present records are the first for the southern hemisphere.…”
Section: Resultsmentioning
confidence: 60%
“…The Paraonidae of Chile have only very recently been reported; Rozbaczylo (1985) listed six species in three genera, recorded for Chile between 1965and 1978. Maurer and Williams (1988 and Mariani et al (1996) provided a few additional records of paraonids sampled off the Chilean coast, but they did not provide exact data on the collection sites.…”
Section: Introductionmentioning
confidence: 99%